What it takes to support a loved one with FASD - Reid, Dorothy; Laplante, Simon; Marnoch, Ray; Roberts, Tammy; Noah, Jennifer; Schmidt, Sonja; Beland, Wanda; Mohr, Shana (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
This photovoice project was undertaken by the Family Advisory Committee of the Canada Fetal Alcohol Spectrum Disorder (FASD) Research Network to describe the experiences and the challenges faced by those supporting loved ones with FASD. Photovoice is a method of bringing forth the voice of those who are typically marginalized. It is a process by which people can act as recorders and potential catalysts for social action and change. The Family Advisory Committee chose the photovoice technique to communicate both their experiential knowledge and the research knowledge on both the challenges and rewards in supporting individuals with FASD. This photovoice project highlights several themes that are consistent with the results of caregiver research and provide a glimpse into the experience of those supporting loved ones with FASD. Through this type of knowledge translation the Family Advisory Committee hopes to enhance policy maker and service provider understanding of the necessity of providing support and services not only to the individual with FASD but to those who support them as well.